The Influence of RADEC Learning (Read, Answer, Discuss, Explain, Create) assisted by Media Handouts and Students' Curiosity on the Ability to Understand Mathematical Concepts - Yulia Alimatus Sakdiah; Ahmad Mukhayat; Kenny Candra Pradana (Universitas Sang Bumi Ruwa Jurai, 2023)
This research was conducted at MTs Nurul Hidayah with the aim of knowing (1) the effect of the Read, Answer, Discuss, Explain, Create (RADEC) learning model assisted by Handout media on understanding mathematical concepts; (2) the influence of students' curiosity on the ability to understand concepts; and (3) the interaction of the handout-assisted RADEC learning model and students' curiosity about their ability to understand mathematical concepts. The research method used was quasy experiment with the non-equivalent group design. The collection of research data was obtained from tests of students' ability to understand concepts and curiosity questionnaires. This research was conducted on class VIII students of MTs Nurul Hidayah with a total of 60 students who were selected through cluster random sampling technique. Based on hypothesis testing through two-way ANOVA, it was obtained (1) there was an influence of the Read, Answer, Discuss, Explain, Create (RADEC) learning model assisted by Handout media on understanding mathematical concepts, (2) there was an influence of students' curiosity on the ability to understand concepts, (3) there is no interaction of the handout-assisted RADEC learning model and students' curiosity about their ability to understand mathematical concepts.